Effects of long-term low intensity silviculture and habitat on birds in Nothofagus antarctica forests of south Patagonia - Benitez, Julieta; Barrera, Marcelo Daniel; Sola, Francisco Javier; Blazina, Ana P.; Martínez Pastur, Guillermo José; Peri, Pablo Luis; Lencinas, María Vanessa (Elsevier, 2022)
Low intensity silviculture has been used to decrease the impact of forest harvesting, for example, on bird species and structural diversity. The objective of this work was to analyse the long-term effect of thinning on bird communities of Nothofagus antarctica forests in Tierra del Fuego (Argentina), compared with unthinned forests at two different locations. Thinning was performed 15 and 50 years ago at each location (ranches), therefore we also evaluated other common forest habitat types to differentiate these effects (location and time). We sampled four habitat types associated to overstory canopy cover (CC) categories: thinned (35–65% CC), and three unthinned forests (open with <35% CC, closed with 65–85% CC, and very closed with >85% CC), totalling 32 sampling sites (2 ranches × 4 canopy cover × 4 replicates). Bird assemblages’ structure and functional traits (e. g., richness, density, trophic groups, use of strata) were surveyed during two consecutive summers (2017–2020) at each site. We also characterized habitats by: (i) forest structure and ground cover (e.g., basal area, debris, and saplings); and (ii) food availability, considering understory plants consumed by birds (e.g., plant richness, grasses and dicots cover) and arthropods (e.g., total abundance). We evaluated the effect of CC, ranch, time, habitat and food availability by Generalised Linear Mixed Models and multivariate analyses (Multiple Response Permutation Procedure, Canonical Correspondence Analysis). In thinned forests, some bird structure and functional traits remained similar to closed forests; however, thinning increased bird species richness, being more similar to open forests. Effect of time could not be detected. CC and ranch were the factors that better described bird community structure, while forest structure, ground cover and food availability (e.g., dominant height, basal area, proportion of Hymenoptera) were the main drivers of most functional traits. The whole bird assemblage was better explained by 4–6 habitat structure and food availability variables depending on location (ranch). Results suggest thinning will benefit bird conservation if thinned forests maintain characteristics of mature forests (e.g., basal area > 40 m2/ha, shrub cover > 5%).